BREAKING DOWN THE CONCEPT OF FEMININE MYSTIQUE IN ESTI KINASIH’S CEWEK!!! - Kusumaningtyas, Dwi N C; Nugroho, Bayu Aji (Fakultas Ilmu Budaya, Universitas Mulawarman, 2022)
Indonesian literature has various experiences of development based on the dynamics of literary thought in their work. One of the literary works that are currently developing is popular literature. The study of popular literature is an interesting study to do. Research on popular literary works is also rarely done by academics. The novel with the title CEWEK!!!, is one of the popular literary works that the researcher examines using Betty Friedan's mystical feminine theory approach. The study is based on the existence of construction that forces women to fulfill their femininity. Breaking of the mystic feminine construction is studied in more depth descriptively through the text sources contained in the novel. The results of the study show that there is an effort to break the mystical feminine construction that has developed in society through three female figures, Langen, Febi, and Fani. The female characters with their awareness have reconstructed the mystical feminine concept to show that women are also superior in society. Keywords: Popular Literature, mystic feminine, novels